2009
DOI: 10.4065/84.9.801
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization to Visualize Genetic Abnormalities in Interphase Cells of Acinar Cell Carcinoma, Ductal Adenocarcinoma, and Islet Cell Carcinoma of the Pancreas

Abstract: (interphase FISH) of acinar cell carcinoma, ductal adenocarcinoma, and islet cell carcinoma of the pancreas. Acinar cell carcinoma and ductal adenocarcinoma, which are nonendocrine tumors, and islet cell carcinomas, which are neuroendocrine tumors, reportedly occur in less than 1%, 95%, and 5%, respectively, of patients with pancreatic cancer. 3,8,9 In 2 retrospective studies of large series of patients, median survival for unresected ductal adenocarcinoma was 3 months ; and for functional islet cell carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, when atypia was interpreted as a positive result, the difference between the sensitivity of routine cytology and FISH was not statistically significant in both groups, whereas the specificity of routine cytology with atypia remained significantly higher than that of FISH in group B. Dewald et al 18 observed chromosomal alterations in 80% of patients with pancreatic cancer with the use of FISH. The similar frequency of chromosomal aneuploidy has been reported in cases of bile duct carcinomas.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, when atypia was interpreted as a positive result, the difference between the sensitivity of routine cytology and FISH was not statistically significant in both groups, whereas the specificity of routine cytology with atypia remained significantly higher than that of FISH in group B. Dewald et al 18 observed chromosomal alterations in 80% of patients with pancreatic cancer with the use of FISH. The similar frequency of chromosomal aneuploidy has been reported in cases of bile duct carcinomas.…”
Section: Discussionmentioning
confidence: 87%
“…Such molecular changes have been observed in approximately 80% of biliary and pancreatic cancers. 17,18 According to previously published reports, FISH enhances the sensitivity of routine brush cytology in the diagnosis of bile duct strictures. However, no investigations have been performed yet to evaluate the role of FISH in detection of malignant pancreatic strictures.…”
Section: Introductionmentioning
confidence: 78%
“…Trisomy of 3 is described in patients with acinar cell carcinoma of pancreas, but we have seen isolated in one adenocarcinoma. 13 Also, trisomy of 7 can occasionally be seen in nonpancreatic benign inflammatory conditions. 14 Therefore, isolated chromosomal abnormalities have to be carefully interpreted within the clinical data and EUS findings as many minor chromosomal abnormalities can be present in benign pancreatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reports have shown that fluorescence in situ hybridisation (FISH) may be used to detect chromosomal abnormalities in malignant cells 12 13. A previous study found quantitative changes in chromosomes 3, 5, 7, 9, 13, 17, 18 and 22 in PDA 12. The alterations reported in pancreatic cancers have shown very high rates of loss of chromosome regions 18q (90%), 17 p (90%), 1 p (60%) and 9 p (85%) as well as moderately frequent losses at nearly a dozen additional sites in 25%–50% of cases 14 15.…”
Section: Introductionmentioning
confidence: 90%